Rules of thumb for chemical engineers : a manual of quick, accurate solutions to everyday process engineering problems - Branan, Carl R. (Elsevier, 2005)
Fluid flow - Heat exchangers - Fractionators - Absorbers - Pumps - Compressors - Drivers - Separatores/accumulators - Boilers - Cooling towers - Refrigeration - Gasification - Gas treating - Vacuum systems - Pneumatic conveying - Blending - Process evaluation - Reliability - Metallurgy - Safety - Controls - Troubleshooting - Starup - Energy conservation - Shortcut methods for decisions - Process modeling using linear programming - Properties - Approximate conversion factors - Appendixes.